ANALYSIS OF BUSINESS DEVELOPMENT BASED ON MANGROVE IN THE DAMAS BEACH DISTRICT TRENGGALEK - pudji purwanti; edi susilo; dwi setijawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
Mangrove forests in Damas coastal has many switching function as plantations, causing a reduction in mangrove forest areas. The decline in mangrove forest area as a result of conversion to palm plantation committed by some members of the group LMDH